Networked and event-triggered control approaches in cyber-physical systems - Zhang, Jinhui, 1982- (CRC Press, 2022)
"This book researches the networked delay compensation and event-triggered control approaches for a series of CPSs subject to network-induced uncertainties. To reduce computational burden of the controller and loads of the network communication, event-triggered control methods are further proposed in this book"--